The Use Of Facebook To Improve Students’ Writing Skill: An Experimental Study At The Second Grade Students Of SMAN 1 Batukliang Utara In Academic Year 2025/2026 - Masyudi, Masyudi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This particular research was intended to reveal any significant effect of using Facebook in improving students’ writing skill and to what extent Facebook contributed to the development of students’ writing skill. Besides that, this research also tried to know how the students respond toward the use of Facebook in teaching writing. This research was experimental research in which the researcher employed the two groups design where the control and experimental group were given pre-test before treatment and post-test after the different treatment that has been given. The population of this research was all the second-grade students of SMAN 1 Btukliang Utara in academic year 2025/2026 while the sample for this research was taken using cluster random sampling technique, then taken XI IPA 5 as the control group and XI IPA 6 as the experimental group. The data collection was done through test and questionnaire. The mean score of control class (MX= 19.18 > MY = 8) then further analyzed using t-test, found that t count > t table, where t-count = 2.90 and t-table = 1.99 at 5% level of significant and according to the existing criteria that the differences between control group and experimental group were significant. And referring to the mean score, it was also found that the experimental class, which was taught using Facebook had the better ability in writing than the students in control class which were taught using traditional media. In other words, Facebook can significantly improve the students’ writing skill. Data about the students’ response were analyzed using Mi (ideal mean) and ISD (ideal standard deviation) formulas with five scales conversion guide. The questionnaire data analysis found that most of the students responded the use of Facebook in teaching English writing at the level “very good”. In other words, Facebook can increase students’ motivation and the potential of Facebook to be utilized in English class especially writing class.